Guía didáctica de embriología humana para fortalecer el aprendizaje en los estudiantes del segundo BGU de la unidad educativa “Amelia Gallegos Díaz” ubicado en la provincia de Chimborazo, cantón Riobamba, durante el período marzo - junio 2015. - Abarca Abarca, Vilma Mariza (2017)
In the "Amelia Gallegos Díaz" Educational Unit, there was evidence of low qualifications and apathy in the subject of Biology resulting in a minimum or low learning, the causes may be the traditional strategies during the teaching - learning process, and little interest of the Students for Biology, being the antecedent that originated the accomplishment of the present investigation, posing as research objective. To determine the level of development with the use of the Didactic Guide of Human Embryology as a didactic-pedagogical tool to strengthen the meaningful learning in the students of the second course of the BGU. The research is descriptive, applied type, documentary, field and experimental, based on inductive and deductive research because it allows to know the didactic situation regarding the learning of Biology. The instrument used is the survey to obtain data for the 35 students of the second course "A". It describes the process for the analysis of the information obtained by applying the computer blog with web 2.0 tools with interactive activities regarding human embryology of the contents of the second course. In the Alternative Lineament, the "Didactic Guide of human embryology to strengthen the learning of Biology" is presented. The data of the tabulation are statistically and graphically interpreted, and the results of before and after applying the Didactic Guide are described; We test the hypotheses by applying the Chi Square statistic. It is concluded that the presentation of content in the blog of Human Embryology in an organized and creative way with web 2.0 tools contribute to the learning of Biology in the students of the second course, recommending, the usefulness of the strategies and processes proposed in the Guide.